REVERCE: a randomized phase II study of regorafenib followed by cetuximab versus the reverse sequence for previously treated metastatic colorectal cancer patients. (3rd December 2018) - Shitara, K; Yamanaka, T; Denda, T; Tsuji, Y; Shinozaki, K; Komatsu, Y; Kobayashi, Y; Furuse, J; Okuda, H; Asayama, M; Akiyoshi, K; Kagawa, Y; et al.
Abstract: Background: The objective of this randomized phase II trial was to evaluate efficacy and safety of the therapeutic sequence of regorafenib followed by cetuximab, compared with cetuximab followed by regorafenib, as the current standard sequence for metastatic colorectal cancer patients. Patients and methods: Patients with KRAS exon 2 wild-type metastatic colorectal cancer after failure of fluoropyrimidine, oxaliplatin, and irinotecan were randomized to receive sequential treatment with regorafenib followed by cetuximab ± irinotecan (R-C arm), or the reverse sequence [cetuximab ± irinotecan followed by regorafenib (C-R arm)]. The primary end point was overall survival (OS). Key secondary end points included progression-free survival (PFS) with initial treatment (PFS1), PFS with second treatment (PFS2), safety, and quality of life. Exploratory end points included serial biomarker analyses, including oncogenic alterations from circulating tumor DNA or multiple serum or plasma proteins. Results: One-hundred one patients were randomized and eligible for efficacy analysis. Sequential treatment was successful in 86% patients in both arms. Median OS for R-C and C-R was 17.4 and 11.6 months, respectively ( P = 0.0293), with a hazard ratio (HR) of 0.61 for OS [95% confidence interval (CI) 0.39–0.96]. The HR for PFS1 (regorafenib in R-C versus cetuximab in C-R) was 0.97 (95% CI 0.61–1.54), and PFS2 (C in R-C versus R in C-R) was 0.29 (95% CI 0.17–0.50). No unexpected safety signals were observed. The quality of life scores during the entire treatment period was not significantly different between the two arms. Circulating biomarker analyses showed emerging oncogenic alterations in RAS, BRAF, EGFR, HER2, and MET, which were more commonly detected after cetuximab than after regorafenib. Conclusions: The therapeutic sequence of regorafenib followed by cetuximab suggests a longer OS than the current standard sequence.